2010
DOI: 10.1055/s-0029-1242991
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-β, Estrogen Receptor-α, and Progesterone Resistance in Endometriosis

Abstract: Loss of progesterone signaling in the endometrium may be a causal factor in the development of endometriosis, and progesterone resistance is commonly observed in women with this disease. In endometriotic stromal cells, the levels of progesterone receptor (PR), particularly the PR-B isoform, are significantly decreased, leading to a loss of paracrine signaling. PR deficiency likely underlies the development of progesterone resistance in women with endometriosis who no longer respond to progestin therapy. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
155
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(180 citation statements)
references
References 54 publications
11
155
1
7
Order By: Relevance
“…The estrogen plays an important role in the planting and growth of ectopic endometrium (Burney & Giudice 2012). Loss of P 4 signaling in the endometrium may be a causal factor in the development of EMS, and P 4 resistance is commonly observed in women with this disease (Bulun et al 2010). Tsutsumi et al (2011) reported that medroxyprogesterone acetate almost completely antagonized the E 2 -induced CXCL12 production in normal ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…The estrogen plays an important role in the planting and growth of ectopic endometrium (Burney & Giudice 2012). Loss of P 4 signaling in the endometrium may be a causal factor in the development of EMS, and P 4 resistance is commonly observed in women with this disease (Bulun et al 2010). Tsutsumi et al (2011) reported that medroxyprogesterone acetate almost completely antagonized the E 2 -induced CXCL12 production in normal ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriyumda progesteron sinyalinin kaybolması, endometriyozis gelişmesine neden olan bir faktör olabilir ve progesteron direnci geliştiğinden, uzun süreli progestin tedavisine yanıt oluşturmaz. 16 Selektif östro-jen reseptör modülatörler (SERM), farklı dokularda ER'ye bağlanarak agonist veya antagonist etki gös-terirler. Endometriyum üzerinde antagonist etki yaparlar.…”
Section: Selekti̇f öStrojen Reseptör Modülatörleri̇unclassified
“…The initial event may involve deficient methylation of the estrogen receptor ERβ promoter resulting in pathologic overexpression of ERβ in endometriotic stromal cells. Ιt is postulated that alterations in the relative levels of ERβ and ERα in endometrial tissue dictate estradiol-regulated progesterone receptor (PR) expression, such that a decreased ERα-to-ERβ ratio may result in suppression of PR [80]. Based on observations regarding the the etiopathogenesis of the disease, scientific work has been done to confirm suspicions that human endometriosis may result from toxic exposure [81,82].…”
mentioning
confidence: 99%